2020
DOI: 10.3390/su12156196
|View full text |Cite
|
Sign up to set email alerts
|

Strongly and Loosely Bound Water in Ambient Particulate Matter—Qualitative and Quantitative Determination by Karl Fischer Coulometric Method

Abstract: Simple physical characterization of water evaporation can provide detailed information regarding its component distribution in particulate matter (PM) samples. The water presence in PM can greatly influence its polarity and subsequent reaction activity, for example, in secondary inorganic and organic matter formation. In this study, the presence of PM-bound water is detected using the Karl Fischer titration method in a temperature gradient with an aim to quantitatively assess different types of water occurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…Teflon filters were selected for their hydrophobic property, reducing the background water signal in the system. Widziewicz-Rzońca et al (2020) also showed that Teflon filters absorb less water than other filter materials. The flow rate in the sampling system was 16.7 L min -1 .…”
Section: A C C E P T E D Mmentioning
confidence: 96%
See 1 more Smart Citation
“…Teflon filters were selected for their hydrophobic property, reducing the background water signal in the system. Widziewicz-Rzońca et al (2020) also showed that Teflon filters absorb less water than other filter materials. The flow rate in the sampling system was 16.7 L min -1 .…”
Section: A C C E P T E D Mmentioning
confidence: 96%
“…Several studies have measured particulate-bound water (PM-bound water) with the offline filter-based Thermal ramp Karl-Fisher (tr-KF) method (Canepari et al, 2013;Perrino et al, 2016;Widziewicz-Rzońca et al, 2020). In that method, Teflon filters are conditioned at 50% RH to investigate the PM-bound water of each chemical component (Perrino et al, 2016) and the characteristic strength (i.e., strongly or loosely) of the bound water (Widziewicz-Rzońca et al, 2020). Dai et al (2021) modified the Dry-Ambient Aerosol Size Spectrometer (DAASS) (Stanier et al, 2004) to estimate the AWC in-situ through the aerosol size change at different RH levels.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The iodine values of the tested biodiesel were determined by titration with 0.01 N sodium thiosulfate compound until the appearance of a light blue color. The water content in the biodiesel was analyzed using volumetric Karl Fischer titration (Model DL-31, Mettler-Toledo Inc., Greifensee, Switzerland), based on the coulometric method [9]. In order to determine the sample's moisture, the Karl Fischer solution was titrated into the biodiesel sample until the first trace of excess iodine appears.…”
Section: Measurement Of Fluid Characteristics Of Biodiesel From Feedsmentioning
confidence: 99%
“…% did not cause the variation of the yield of fatty acid methyl ester (FAME) at 130 • C. In contrast, some studies found that sufficient water content, such as 2.5 wt. %, in raw oil might enhance hydrolysis of fatty acids, which leads to activation of the transesterification reaction [9]. Sun et al [10] studied the effect of water content in wet Nannochloropsis oceanica on 1-butyl-3-methylimidazolium hydrogen sulfate ([Bmim][HSO 4 ])-catalyzed in situ transesterification.…”
Section: Introductionmentioning
confidence: 99%
“…Metodę piecykową stosowano także do analizy zawartości wilgoci w proszkach metali (Mellin et al, 2020), w próbkach 1-oktanolu nasyconego wodą, cementu, węgla i rafinowanego oleju (Margolis et al, 2004a), a także w filtrach cząstek stałych. W tym ostatnim przypadku metoda pozwoliła na ilościową ocenę różnych rodzajów wody (luźno związanej, absorpcyjnej i krystalicznej) (Canepari et al, 2013;Rogula-Kozłowska et al, 2017;Widziewicz-Rzońca et al, 2020). Margolis et al (2004b) wykorzystali metodę z odparowaniem do badania olejów smarowych.…”
Section: Wstępunclassified